The Effect of The Think Aloud Strategy on Students' Reading Comprehension Ability - Burhansyah Burhansyah; Saiful Marhaban; Siti Maisyarah; Syamsul Bahri Ys (Universitas Syiah Kuala, 2022)
This research was designed to figure out the effectiveness of the think aloud strategy in improving students’ reading comprehension ability. The think aloud strategy is a learning strategy whereby students verbalize their thought as they read. Twenty 2nd grade students of MAS Darul Ulum Banda Aceh participated in this quantitative research. This research used a pre-experimental design with one-group pretest-posttest. The finding showed that the think aloud strategy improves students’ reading comprehension ability, especially in analytical exposition text. It can be seen from the mean score of the post-test (54.4) which was higher than that of the pre-test (36.4). The t-test analysis showed that the t-score (4.255) obtained a higher gain than the t-table (2.085). This strategy successfully helped the students to increase their reading comprehension ability in all aspects, particularly in identifying main ideas, making inferences, summarizing, and interpreting vocabulary. Therefore, the think aloud strategy can be considered as an effective instructional tool for teaching reading skill.